2012
DOI: 10.1039/c2cc34015a
|View full text |Cite
|
Sign up to set email alerts
|

A modified guanosine phosphoramidite for click functionalization of RNA on the sugar edge

Abstract: A propargyl containing guanosine phosphoramidite was synthesized and incorporated into siRNA, enabling click-ligation with an azido fluorophore onto the nucleobase sugar edge. Duplex stability was not affected by labeling at this new site, which allowed deconvolution of the effects of label, structure and attachment site on RNAi activity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
19
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 32 publications
2
19
0
Order By: Relevance
“…After hybridization of clicked sense-strand derivatives to the appropriate antisense strand, cells were incubated with a concentration series of siRNA double strands and eGFP fluorescence emission measured by FACS 24 h later. In keeping with our previously reported identification of a permissive attachment site on the 3′-end of the sense strand (70), conjugation of various azides did not significantly increase the IC 50 values (Figure 6D). Indeed, the *PDI derivative (pink in Figure 6) showed an IC 50 value improved by ~3-fold.…”
Section: Resultssupporting
confidence: 92%
“…After hybridization of clicked sense-strand derivatives to the appropriate antisense strand, cells were incubated with a concentration series of siRNA double strands and eGFP fluorescence emission measured by FACS 24 h later. In keeping with our previously reported identification of a permissive attachment site on the 3′-end of the sense strand (70), conjugation of various azides did not significantly increase the IC 50 values (Figure 6D). Indeed, the *PDI derivative (pink in Figure 6) showed an IC 50 value improved by ~3-fold.…”
Section: Resultssupporting
confidence: 92%
“…Earlier reports on alkylation of the exocyclic guanosine amine had suggested minimal impact on duplex stability for single substitutions, and had also reported that significant differences in melting temperature of modified duplexes were only evident upon a double methylation ( 17 19 ). In agreement with this finding, our results showed that mono-labeling on the sugar edge of guanosine via its exocyclic amine had little impact on structure and RNAi activity of an siRNA labeled on the 5′ of the antisense strand ( 16 ). However, data on the impact of propargyl groups on exocyclic amines inside helices are still amiss.…”
Section: Introductionsupporting
confidence: 88%
“…The DNA strand corresponds in sequence to the passenger strand of an anti-eGFP siRNA which we had used in previous studies ( 16 ). To investigate the stability of helices containing propargylated cytidines, the respective oligodeoxynucleotides were thus hybridized (i) to an oligoribonucleotide identical to the antisense strand of the corresponding siRNA, and (ii) to an oligodeoxynucleotide of identical sequence.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We have previously validated several such FRET-siRNA systems qualitatively ( 37 ) and quantitatively ( 38 ) using EGFP as a reporter gene. The knockdown was routinely measured 24 h after transfection, and reached close to perfect (>95%) knockdown levels.…”
Section: Introductionmentioning
confidence: 99%